2010
DOI: 10.1007/s12257-009-3064-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactor surface on production of bacterial cellulose and water soluble oligosaccharides by Gluconacetobacter hansenii PJK

Abstract: The effect of agar plates on the bacterial cellulose (BC) production in a static culture was investigated in order to find the role of agar component as a surface modifying agent. Two types of surface modified reactors (SMRs: SMRD and SMRB) were prepared by coating the bottom of the reactors with agar dissolved in distilled water and basal medium, respectively. The SMRs were used for BC and water soluble oligosaccharides (WSOS) production. Control was done by the same procedure using reactors without agar plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…The fraction Iα and Iβ mixture of allomorphs was attributed to the cultivation condition of the bacteria and also the ratio of cellulose, which may differ according to bacterial strain. All of these results were consistent with earlier published X-ray data for BC obtained with other bacteria [7,25,26,[29][30][31][32][33][34]. However, compared with other bacteria, the peaks of BC produced by Leifsonia sp.…”
Section: Production and Optimization Of Bcsupporting
confidence: 92%
“…The fraction Iα and Iβ mixture of allomorphs was attributed to the cultivation condition of the bacteria and also the ratio of cellulose, which may differ according to bacterial strain. All of these results were consistent with earlier published X-ray data for BC obtained with other bacteria [7,25,26,[29][30][31][32][33][34]. However, compared with other bacteria, the peaks of BC produced by Leifsonia sp.…”
Section: Production and Optimization Of Bcsupporting
confidence: 92%
“…It was reported by several authors that the loose fibril arrangement and large size of pores enhance the water capacity of BC [70,71]. It is considered that closely arranged microfibrils bind the water molecules more efficiently due to the stronger hydrogen bonding interactions, as compared to the loosely arranged microfibrils [72,73]. Furthermore, it was demonstrated that more water can be retained due to the larger surface area provided by thinner and longer fibers [74].…”
Section: Discussionmentioning
confidence: 98%
“…The increase in Ch incorporation over the treatment time shown in the SEM analysis increased the WHC of the BC-Ch composite. The increased penetration of Ch results in better hydrogen bonding interaction between the BC and Ch molecules, which is also a factor causing an increase in the water holding capacity [30]. Nearly the same WHC for the BC-Ch composites prepared with 20 or 40 hrs of treatment indicates that the BC was almost saturated with Ch in 20 hrs of treatment.…”
Section: Water Holding Capacity and Water Release Ratementioning
confidence: 99%